The Urgency of Social Skills for Adolescents and Religious Relationships with the Environment of Life (Study on Adolescents of Ogogasang Village, Dondo District, Tolitoli) - Muhammad Fadhil; M. Hulkin; Zulfi Idayanti; ⁠Muh. Asharif Suleman; Basri (Sosial Horizon: Jurnal Pendidikan Sosial, 2024)
Social skills are also important for adolescents in identifying and managing their internal conflicts and feelings, which in turn helps in emotional and stress management. This study aims to examine the importance of social and religious skills in adolescents and their relationship with their living environment, with a particular focus on adolescents in Ogogasang Village, Dondo Sub-district, Tolitoli District. Social and religious skills are two important aspects of adolescent development that affect various aspects of their lives, including social interaction, academic achievement and psychological well-being. This research used a descriptive qualitative method with a case study approach to explore an in-depth understanding of the phenomenon under study. Data were collected through in-depth interviews, observations, and document analysis. The results showed that adolescents who have good social and religious skills tend to have more harmonious relationships with family and peers, and show better adaptation in their social environment. A supportive living environment also plays a significant role in the development of these skills. In conclusion, social and religious skills play a crucial role in the lives of adolescents, and their development deserves special attention from parents, educators and society. The implications of this study show the importance of an integrated approach in developing social and religious skills. Social skills are also important for adolescents in identifying and managing their internal conflicts and feelings, which in turn helps in emotional and stress management. This study aims to examine the importance of social and religious skills in adolescents and their relationship with their living environment, with a particular focus on adolescents in Ogogasang Village, Dondo Sub-district, Tolitoli District. Social and religious skills are two important aspects of adolescent development that affect various aspects of their lives, including social interaction, academic achievement and psychological well-being. This research used a descriptive qualitative method with a case study approach to explore an in-depth understanding of the phenomenon under study. Data were collected through in-depth interviews, observations, and document analysis. The results showed that adolescents who have good social and religious skills tend to have more harmonious relationships with family and peers, and show better adaptation in their social environment. A supportive living environment also plays a significant role in the development of these skills. In conclusion, social and religious skills play a crucial role in the lives of adolescents, and their development deserves special attention from parents, educators and society. The implications of this study show the importance of an integrated approach in developing social and religious skills.